2008
DOI: 10.3892/ijmm.22.1.25
|View full text |Cite
|
Sign up to set email alerts
|

RhoA protein expression in primary breast cancers and matched lymphocytes is associated with progression of the disease

Abstract: RhoA protein is over-expressed in breast cancer and other solid tumors and has been used in tumor biopsies as a quantitative tumor marker for progression, stage and prognosis in molecular detection strategies. Measuring protein markers in plasma or blood cells is preferred to tumor biopsies as it represents a minimally invasive, repeatable measurement that can be followed over time. In this study we evaluated the hypothesis that quantitative RhoA protein expression in circulatory lymphocytes is identically ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…Together, our study further substantiates an important role for LMO7 in breast cancer metastasis. Therapeutically, although an increased expression of Rho was also demonstrated in metastatic breast cancer (4,5,9,16,27,56,60), Rho may not be a specific target, given its expression in normal cells and its involvement in regulating other important cell functions. LMO7, however, is a cell-specific protein and is not expressed in normal breast tissues (19,47).…”
Section: Figmentioning
confidence: 99%
“…Together, our study further substantiates an important role for LMO7 in breast cancer metastasis. Therapeutically, although an increased expression of Rho was also demonstrated in metastatic breast cancer (4,5,9,16,27,56,60), Rho may not be a specific target, given its expression in normal cells and its involvement in regulating other important cell functions. LMO7, however, is a cell-specific protein and is not expressed in normal breast tissues (19,47).…”
Section: Figmentioning
confidence: 99%
“…Enhanced RhoA activity in the cancer cells is mostly due to RhoA overexpression because mutation of RhoA has not been found in human cancers (33,34). Accumulating evidences have shown that upregulation of RhoA mRNA and RhoA protein levels has been well documented in various human cancers (29,30,35). The present study suggests one potent mechanism of epithelial RhoA overexpression via wound-induced NAG-1.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, the current study observed elevation of total level of RhoA protein. Upregulation of RhoA expression has been also observed in various types of human cancer cells (29)(30)(31), and one suggested deciphering of the oncogenic induction of RhoA expression is the signaling orchestration by Myc-Skp2-Miz1-p300 transcriptional complex (32). Enhanced RhoA activity in the cancer cells is mostly due to RhoA overexpression because mutation of RhoA has not been found in human cancers (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It is also well-known that tumors are stiffer than the surrounding stromal tissue. This stiffening is likely a result of increased interstitial tissue pressure and solid stress due to tumor expansion [120], an increase in the intracellular stiffness of malignant cells [121], excessive RhoA-based cell contractility [122,123], and fibrosis [105]. Furthermore, patients presenting clinically with fibrotic tumors typically have a poor prognosis [124].…”
Section: Basal Lamina Stiffness Drives the Malignant Phenotype Througmentioning
confidence: 99%